2018
DOI: 10.1186/s12957-018-1445-z
|View full text |Cite
|
Sign up to set email alerts
|

Are ADC values of readout-segmented echo-planar diffusion-weighted imaging (RESOLVE) correlated with pathological prognostic factors in rectal adenocarcinoma?

Abstract: BackgroundDiffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) values as imaging biomarkers of rectal cancer are currently a hot research spot. The use of ADC values for preoperative judgment of pathological features in rectal cancer has been generally accepted. The image quality evaluation of conventional diffusion is severe deformation, and the measurement of ADC values can easily lead to bias. Readout-segmented echo-planar diffusion-weighted imaging (RESOLVE) provides high signal-to-noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The results of the quantitative and qualitative analysis indicate that the image quality of RESOLVE DWI is better than that of SS-EPI DWI. The technique of RESOLVE DWI has proven to provide better detection and image quality in rectal, prostate, kidney, neck, and breast compared with SS-EPI DWI [ 15 , 16 , 18 , 35 , 36 ]. Our study also supports this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the quantitative and qualitative analysis indicate that the image quality of RESOLVE DWI is better than that of SS-EPI DWI. The technique of RESOLVE DWI has proven to provide better detection and image quality in rectal, prostate, kidney, neck, and breast compared with SS-EPI DWI [ 15 , 16 , 18 , 35 , 36 ]. Our study also supports this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown by NCCN, degree of differentiation, T stage, and N stage are powerful prognostic factors for patients with rectal cancer [3]. Several studies showed a statistically significant correlation between the apparent diffusion coefficient value, derived from diffusion-weighted images, and tumor differentiation grade [16, 17]; however, some studies showed a contradictory result [18, 19]. In this study, radiomics and tumor differentiation grade showed a statistically significant correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown by NCCN, degree of differentiation, T stage, and N stage are powerful prognostic factors for patients with rectal cancer [3]. Several studies showed a statistically significant correlation between the apparent diffusion coefficient value, derived from diffusion-weighted images, and tumor differentiation grade [16,17]; however, some studies showed a contradictory result [18,19]. In this study, radiomics and tumor differentiation grade showed a statistically significant correlation.…”
Section: Discussionmentioning
confidence: 42%